ISPC Commentary on the Revised Proposal for CRP1.2 - September 2012 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2012)
ISPC Commentary on CRP 1.2 "Humidtropics: Integrated systems for the humid tropics" (Version of 15 August 2012)